Factors Associated with Long-Acting Reversible Contraception (LARC) use in Postpartum Women at Srinagarind Hospital - Srimeunwai Akesittipaisarn; Yuthapong Werawatakul; Saksin Simsin (The Royal Thai College of Obstetricians and Gynaecologists, 2018)
Objectives: To determine the associated factors those predict the use of long-acting reversible contraception (LARC) among postpartum women at Srinagarind Hospital.Materials and Methods: A cohort study of postpartum women was conducted at Srinagarind Hospital from May to October 2016. LARC methods were defined as progestogen-only injectable contraceptives, intrauterine devices, and contraceptive implants. The participants were interviewed during admission to the postpartum ward in order to ascertain baseline information, as well as information regarding their intention to use or not to use LARC. The participants were interviewed again after their six week postpartum visit about the contraceptive method they actually used. Data of participants who did not appear for their six-week postpartum visit were obtained by telephone interview within 6-12 weeks after delivery. Logistic regression analysis was applied to determine the factors associated with LARC use.Results: The mean age of the participants was 28.4 ± 5.7 years. One hundred twenty-six out of a total of 312 participants (40.4%) reported using LARC. The methods of LARC used were depot medroxyprogesterone acetate (DMPA) (82.5%) and contraceptive implants (17.5%). Participants who were more likely to use LARC included those who had expressed their intention to use LARC during the first interview, current students, and women whose medical expenses were covered by universal coverage scheme.Conclusion: Rate of LARC use in this study was approximately 40%. The most common method of LARC used was DMPA. Significant independent factors affecting the use of LARC were participants' intentions, occupation, and type of health care coverage.